APCB's Abstracts 2: 9th Asian Pacific Congress on Bronchology and Interventional Pulmonology - Asia-Pacific Congress Bronchology-Interventional Pulmonology (The Interventionalist Journal, 2023)
MYSIR’s Abstracts 2 1. EP01: LARGEST CASE SERIES OF FLEXIBLE BRONCHOSCOPY REMOVAL OF ASPIRATED SCARF PINS 2. EP02: TO COMPARE THE EFFICACY AND DIAGNOSTIC YIELD OF BRONCHOSCOPIC BIOPSY USING CONVENTIONAL FORCEPS VERSUS 1.1MM CRYOPROBE IN CENTRAL AIRWAY LESION 3. EP03: PREDICTIVE RISK FACTORS FOR PNEUMOTHORAX AFTER FLUOROSCOPIC GUIDED TRANSBRONCHIAL LUNG BIOPSY 4. EP04: THE EFFICACY OF BRONCHIAL WASHING AND BRONCHOALVEOLAR LAVAGE IN SUSPECTED PULMONARY TUBERCULOSIS IN ASIAN POPULATION 5. EP05: BRONCHOSCOPIC MANAGEMENT OF PEDIATRIC BENIGN TRACHEO-BRONCHIAL STENOSIS: A RETROSPECTIVE STUDY